2020
DOI: 10.1016/j.numecd.2020.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Association between coronary atherosclerosis and visceral adiposity index

Abstract: Background and aims: Visceral obesity is a marker of dysfunctional adipose tissue and ectopic fat infiltration. Many studies have shown that visceral fat dysfunction has a close relationship with cardiovascular disease. For a better identification of visceral adiposity dysfunction, the visceral adiposity index (VAI) is used. Coronary artery calcium score (CACS) is known to have a strong correlation with the total plaque burden therefore provides information about the severity of the coronary atherosclerosis. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 30 publications
2
50
0
2
Order By: Relevance
“…Moderate to high CACS, defined as >100 in the present study, is associated with moderate atherosclerotic plaque burden [18,24,25]. In a recent study from Hungary, VAI was associated with a CACS >100, but this association was only detected in men [13]. Here, we found a significant association between NVAI and CACS >100 in both men and women.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Moderate to high CACS, defined as >100 in the present study, is associated with moderate atherosclerotic plaque burden [18,24,25]. In a recent study from Hungary, VAI was associated with a CACS >100, but this association was only detected in men [13]. Here, we found a significant association between NVAI and CACS >100 in both men and women.…”
Section: Discussionsupporting
confidence: 68%
“…Although several studies have demonstrated a link between visceral adipose tissue (measured by abdominal CT) and coronary atherosclerosis or arterial stiffness, most of these studies were limited by their small sample size [13,14]. To date, only one study has reported a significant association between VAI and CACS, which was observed only in men [13]. Furthermore, the association of NVAI with coronary atherosclerosis and arterial stiffness are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies confirmed correlations of the VAI with visceral fat distribution and insulin resistance, even in patients with a normal WC. The VAI has been applied in different patient populations, including patients with metabolic syndrome [11,12], diabetes [13], nonalcoholic fatty liver disease [14] and cardiovascular disease [15,16], all of which are often associated with lung function impairment [17][18][19]. There is a lack of data on the association between VAI and lung function impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the gluteofemoral fat was considered as a protective metabolic sink, which stably stores triglycerides to alleviate the ectopic fat deposition and lower the cardiometabolic risks [17]. In contrast, increase of android fat and visceral fat (central adiposity) is independently correlated with higher risk for cardiovascular disease [5,6,15,18]. However, the gold standard method: DXA for quantifying BF% and regional fat mass is not generally accessible in the outpatient clinic since the machine is expensive, space occupied, experienced operator required and radiation exposure involved.…”
Section: Introductionmentioning
confidence: 99%